Making improvements in influenza vaccines: incremental change or transformational evolution?. (March 2009) - Liebowitz, David; Lu, Bin
Influenza is one of the leading causes of morbidity and mortality, with 36, 000 deaths and 226, 000 hospitalizations occurring annually in the USA, primarily in the elderly. The currently licensed influenza vaccines, trivalent inactivated influenza vaccine and live, attenuated influenza vaccine, although effective in many respects, need to be more efficacious for the elderly and the very young. They can also be improved upon to induce broader immunity and cross-protection against drifted or variant strains. Additionally, there is room for improvement in manufacturing technologies. Increased antigen dose, adjuvants, virus-like particles and virosomes, novel live, attenuated influenza vaccines, and universal vaccines are all being developed or have been developed to address the unmet need in the elderly. Many of these approaches may provide incremental improvements in efficacy, where transformative improvement is necessary.